Pharmacological targeting of the hyper-inflammatory response to SARS-CoV-2-infected K18-hACE2 mice using a cluster of differentiation 36 receptor modulator - Gauvin, Jade; Huynh, David N.; Dubuc, Isabelle; Lê, Catherine; Tugores, Rafaela; Flamand, Nicolas; Flamand, Louis; Lubell, William D.; Ong, Huy; Marleau, Sylvie (Frontiers in Pharmacology, 2024)
The scientific and medical community faced an unprecedented global health hazard that led to nearly 7 million deaths attributable to the rapid spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. In spite the development of efficient vaccines against SARS-CoV-2, many people remain at risk of developing severe symptoms as the virus continues to spread without beneficial patient therapy. The hyper-inflammatory response to SARS-CoV-2 infection progressing to acute respiratory distress syndrome (ARDS) remains an unmet medical need for improving patient care. The viral infection stimulates alveolar macrophages to adopt an inflammatory phenotype regulated, at least in part, by the cluster of differentiation 36 receptor (CD36) to produce unrestrained inflammatory cytokine secretions. We suggest herein that the modulation of the macrophage response using the synthetic CD36 ligand hexarelin offers potential as therapy for halting respiratory failure in SARS-CoV-2-infected patients.